2010
DOI: 10.1128/jb.01338-09
|View full text |Cite
|
Sign up to set email alerts
|

PcaO Positively Regulates pcaHG of the β-Ketoadipate Pathway in Corynebacterium glutamicum

Abstract: We identified a new regulator, PcaO, which is involved in regulation of the protocatechuate (PCA) branch of the ␤-ketoadipate pathway in Corynebacterium glutamicum. PcaO is an atypical large ATP-binding LuxR family (LAL)-type regulator and does not have a Walker A motif. A mutant of C. glutamicum in which pcaO was disrupted (RES167⌬pcaO) was unable to grow on PCA, and growth on PCA was restored by complementation with pcaO. Both an enzymatic assay of PCA 3,4-dioxygenase activity (encoded by pcaHG) and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…In vitro EMSA results showed that ATP weakened the binding between PcaO and its target sequence but ADP strengthened this binding, while the effect of protocatechuate on PcaO binding was dependent on the protocatechuate concentration. These findings suggest that in the presence of protocatechuate, the transcription of pcaHG is probably controlled by the ratio of ATP to ADP in cells (Zhao et al 2010). The PcaR-PcaO hierarchical regulatory system in C. glutamicum provides a flexible control that necessary for the degradation of various aromatic compounds that are channeled to the protocatechuate pathway.…”
Section: Regulation Of Aromatic Compounds Metabolism In C Glutamicummentioning
confidence: 96%
See 3 more Smart Citations
“…In vitro EMSA results showed that ATP weakened the binding between PcaO and its target sequence but ADP strengthened this binding, while the effect of protocatechuate on PcaO binding was dependent on the protocatechuate concentration. These findings suggest that in the presence of protocatechuate, the transcription of pcaHG is probably controlled by the ratio of ATP to ADP in cells (Zhao et al 2010). The PcaR-PcaO hierarchical regulatory system in C. glutamicum provides a flexible control that necessary for the degradation of various aromatic compounds that are channeled to the protocatechuate pathway.…”
Section: Regulation Of Aromatic Compounds Metabolism In C Glutamicummentioning
confidence: 96%
“…2a). The pcaR gene encodes a transcriptional regulator of the IclR family and pcaO codes for a transcriptional activator of the large ATP-binding LuxR (LAL)-type regulator family (Brune et al 2005;Zhao et al 2010). PcaR exerts its regulatory role by interacting with 15-bp operator sequences that are located in the pcaI-pcaR intergenic region and upstream of pcaH and pobA.…”
Section: Regulation Of Aromatic Compounds Metabolism In C Glutamicummentioning
confidence: 99%
See 2 more Smart Citations
“…glutamicum is a well-studied, high-GC-content, Gram-positive soil bacterium of industrial importance. The ability of C. glutamicum to metabolize a variety of aromatic compounds has been studied for its type strain, ATCC 13032 (5,15,(41)(42)(43)49). However, no degradation of PAA by C. glutamicum was reported.…”
mentioning
confidence: 99%